2019
DOI: 10.3390/s19235202
|View full text |Cite
|
Sign up to set email alerts
|

Fringe Phase-Shifting Field Based Fuzzy Quotient Space-Oriented Partial Differential Equations Filtering Method for Gaussian Noise-Induced Phase Error

Abstract: Traditional filtering methods only focused on improving the peak signal-to-noise ratio of the single fringe pattern, which ignore the filtering effect on phase extraction. Fringe phase-shifting field based fuzzy quotient space-oriented partial differential equations filtering method is proposed to reduce the phase error caused by Gaussian noise while filtering. First, the phase error distribution that is caused by Gaussian noise is analyzed. Furthermore, by introducing the fringe phase-shifting field and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…It is worth noting that Gaussian filtering improves the quality of fringes without changing the sine of the fringes [5,6]. This is the theoretical premise that step 3 can improve the accuracy of the wrapped phase by regenerating the phase shift fringe images from the wrapped phase.…”
Section: Principles Of the Iterative Phase-correction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that Gaussian filtering improves the quality of fringes without changing the sine of the fringes [5,6]. This is the theoretical premise that step 3 can improve the accuracy of the wrapped phase by regenerating the phase shift fringe images from the wrapped phase.…”
Section: Principles Of the Iterative Phase-correction Methodsmentioning
confidence: 99%
“…For instance, in [5], Gaussian filtering was used to filter the captured phase-shiftfringe images, thereby inhibiting phase errors caused by noise. Other researchers [6] have used a fuzzy-quotient spaceoriented partial-differential-equations filtering method to suppress Gaussian noise in captured images and improve phase accuracy. In [7], median filtering was used to preprocess captured images and filter out invalid data using a masking algorithm to improve the accuracy and precision of the phase solution.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we introduce the theory of fuzzy quotient space [35][36][37][38][39], and propose the dynamic granularity matrix space model. Considering the consistence of granularity division and image segmentation theory, a dynamic granularity matrix space model is proposed, and the problem of image segmentation can be reconstructed based on the DGMS model.…”
Section: B Dynamic Granularity Matrix Space Modelmentioning
confidence: 99%
“…According to Theorem 8, through the inclusion relation of quotient sets, the cluster of quotient sets will generate an ordered chain, that is, a hierarchical structure [35][36][37][38]. According to Theorem 8-9, a fu zzy equivalence relation corresponds to a hierarchical structure, also corresponds to a distance function.…”
Section: Ab  Must Have Solution On (X F T)mentioning
confidence: 99%
“…Yu et al [ 25 ] proposed a fringe phase-shifting, field-based, fuzzy quotient, space-oriented, partial differential equations filtering method, to reduce the phase error caused by Gaussian noise while filtering. Experiments demonstrated that the method achieves a higher signal-to-noise ratio and lower phase error caused by noise, while also retaining more edge details.…”
mentioning
confidence: 99%